A new species of Paracleistostoma De Man, 1895 (Crustacea: Decapoda: Brachyura: Camptandriidae) from Haikou, Hainan Province, China - Liu, Han Lun; Huang, Jian Rong (Zootaxa, 2016)
A new species of Paracleistostoma De Man, 1895, P. meilanense n. sp. is reported from mangroves forests in Haikou, Hainan Province, China. The new species inhabits mud burrows in the upper intertidal zone and is sympatric with P. tomentosa Yang & Sun, 1993, and P. depressum De Man, 1895. The slender chelipeds as well as the characteristic morphology of the male first pleopod easily distinguishes the species from congeners.